Are ethical issues becoming prevalent among business management researchers? - Ayodele, Freida Ozavize; Cheng, Eaw Hoo; Hasnah, Haron; Dabor, Eyasan Leslie (Universiti Malaysia Pahang, 2020)
This study investigates the prevalence of unethical issues among businessmanagement researchers based on retraction publications from the retraction watch database. Forty-two publications retracted between 2007 and 2019 were analyzed based on the frequency of retraction over time, Journals’ impact factors, the type of Journals, the publisher, and the nature of the misconduct. The retraction analysis revealed that research misconduct in business management research is fast evolving around known and emerging themes. The study, therefore, suggests business academics stakeholders rethink the institutional policies for better moral based publication strategies to tackle the upsurge and promotes the continuous supply of reliable information necessary for decision-making in the business management field.